2019
DOI: 10.1080/2162402x.2019.1665977
|View full text |Cite
|
Sign up to set email alerts
|

First report on two cases of pleomorphic dermal sarcoma successfully treated with immune checkpoint inhibitors

Abstract: Pleomorphic dermal sarcoma (PDS) is one of the most common sarcoma of the skin. Currently, limited treatment options exist for advanced stages of the disease. While immune checkpoint inhibitors (CPIs) have revolutionized cancer treatment options-their efficacy in PDS has not been explored yet. Here, we present two advanced PDS cases that showed response to anti-PD-1 therapy. Patient A had a locally metastasized PDS and reached a complete remission of the disease after eight cycles of Pembrolizumab. Patient B d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
1
20
0
6
Order By: Relevance
“…treatment options, including immune-checkpoint inhibition, as well as iii.) PDGFRB as a potential diagnostic biomarker for PDS, complementing previous studies [ 8 , 9 ].…”
Section: Precision Medicine: Discovering Genetic Alterations and Tumosupporting
confidence: 76%
“…treatment options, including immune-checkpoint inhibition, as well as iii.) PDGFRB as a potential diagnostic biomarker for PDS, complementing previous studies [ 8 , 9 ].…”
Section: Precision Medicine: Discovering Genetic Alterations and Tumosupporting
confidence: 76%
“…High TMB is known to be associated with a better response to immunotherapy with checkpoint inhibitors (CPI) such as anti-PD-1 and anti-PD-L1 across diverse tumor entities [ 42 ]. Interestingly, a case study reported that two patients diagnosed with advanced PDS and high TMB have been successfully treated with anti-PD-1 (Pembrolizumab, (KEYTRUDA ® MSD Kenilworth, NJ, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Another patient with an inoperable relapsed PDS (TMB 77.997 mt/mb) treated with Pembrolizumab for four months, similarly showed a complete response. However, this patient received additional radiotherapy, introducing an additional factor potentially influencing treatment response [ 42 ]. Pembrolizumab is approved for other UV-induced skin tumors, such as malignant melanoma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A PET scan 3 months after commencement of therapy demonstrated a complete response with regression of all sites of metastatic disease (c, d), which is ongoing. This case adds to the evidence that anti‐PD‐1 therapy can be highly effective in patients with advanced PDS 1,2…”
mentioning
confidence: 63%